One-step, Rapid and Green Synthesis of Multifunctional Gold Nanoparticles for Tumor-Targeted Imaging and Therapy - Hua Qin Yin; Guang Shao; Feng Gan; Gang Ye (Nanoscale Research Letters, 2020)
Abstract Gold nanoparticles (GNPs) have always been used as doxorubicin (DOX) transport vectors for tumor diagnosis and therapy; however, the synthesis process of these vectors is to prepare GNPs via chemical reduction method firstly, followed by conjugation with DOX or specific peptides, so these meth•ods faced some common problems including multiple steps, high cost, time consuming, complicated preparation, and post-processing. Here, we present a one-step strategy to prepare the DOX-conjugated GNPs on the basis of DOX’s chemical constitution for the first time. Moreover, we prepare a multifunctional GNPs (DRN-GNPs) with a one-step method by the aid of the reductive functional groups possessed by DOX, RGD peptides, and nuclear localization peptides (NLS), which only needs 30 min. The results of scattering images and cell TEM studies indicated that the DRN-GNPs could target the Hela cells’ nucleus. The tumor inhibition rates of DRN-GNPs via tumor and tail vein injection of nude mice were 66.7% and 57.7%, respectively, which were significantly enhanced compared to control groups. One step synthesis of multifunctional GNPs not only saves time, materials, but also it is in line with the development direction of green chemistry, and it would lay the foundation for large-scale applications within the near future. Our results suggested that the fabrication strategy is efficient, and our prepared DRN-GNPs possess good colloidal stability in the physiological system; they are a potentially contrast agent and an efficient DOX transport vector for cervical cancer diagnosis and therapy.